Eponyms in trichoscopy - Salecha Akshay Jain; Kinnera Boina; Suruthi Purushothaman; Kanmani Indra (Wolters Kluwer Medknow Publications, 2022)
Trichoscopy is a non-invasive scalp and hair dermoscopy. In our daily dermatology practice, many eponyms are used. The present article highlights various eponyms in trichoscopy described in dermatology.